SnowApp-ilmastopalvelu talvimatkailukeskuksille - Mettiäinen, Ilona; Coath, Martin; Contreras, Roxana; Toivonen, Jusu (Zenodo, 2020)
An information slide on our SnowApp climate service for winter tourism industry in Northern Finland, presented during the Lapland Tourism Parliament 2020 (29.-30.10.2020 Olos, Finland).